MECHANISMS FOR THE EFFECTIVE USE OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN THE INFORMATION-EDUCATIONAL ENVIRONMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
This article scientifically analyzes the pedagogical, technological, and organizational mechanisms for the effective use of artificial intelligence (AI) technologies in the information-educational environment. The article highlights the potential of AI in personalizing the learning process, determining students’ levels of knowledge, creating digital tools that assist teachers, and optimizing learning activities. The study examines the impact of AI-based learning platforms, adaptive testing systems, learning-process monitoring algorithms, and analytical software on educational effectiveness. The article also addresses issues of security, ethical standards, and pedagogical responsibility in implementing AI technologies in educational practice, and presents proposals and recommendations for their effective use. The results contribute to enhancing the importance of AI technologies in the process of digitalizing the information-educational environment.